Maternal anesthesia for EXIT procedure: A systematic review of literature - Kamal Kumar; Cristiana Miron; Sudha Indu Singh (Wolters Kluwer Medknow Publications, 2019)
The ex utero intrapartum treatment (EXIT) procedure is performed in cases of fetal congenital malformation. The anesthetic management is much more challenging and involves providing profound uterine relaxation, maintenance of Uteroplacental blood flow and fetal anesthesia. The aim of the article is to review the literature and compare the efficacy of both the anesthetic techniques with respect to maternal and fetal outcomes. The literature source for this review was obtained via PubMed, Medline, Google scholar and Cochrane database of systematic reviews until January 2017. In our literature review we found that both GA and Regional anesthesia were successfully described for EXIT procedure but GA was performed in the majority of cases.Consideration for anesthetic technique should be done on a case-by-case basis.